Import penetration rate in view of a new concept of measuring foreign trade - Fronczek, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article discusses the issue of import market penetration (IPR). The formula that has been in use so far assumes that the products manufactured and exported by a given country do not contain any foreign value and, likewise, the goods imported by a country do not contain any domestic value. In today’s open economy, however, the models taking such assumptions significantly distort the picture of the reality. The new concept on measuring foreign trade based on added value is an attempt at eliminating this limitation. Accordingly, it would be justifiable to modify the formula of the indicator so that it could account for the foreign value in the production and exports, while leaving out the domestic value in imports. The article is an attempt to develop such a formula and apply it to the assessment of the import penetration rate for the EU-15 countries. It was assumed that the inclusion of foreign value in the domestic production would cause the import penetration rate to be higher than in the case of using the old formula. The calculations were conducted with data from the OECD-WTO Database and WIOD Database. The results for the selected years from the period 1995-2011 did not allow to unequivocally confirm the hypothesis in the case of the selected group of countries. They show, however, that the import penetration rate in the EU-15 countries has risen irrespective of the method applied. On the other hand, the value of the modified indicator for agricultural and industrial goods in total was on average lower that the values calculated using the standard method by approximately 6-10 percentage points. The modified IPR was lower than the traditional one for textiles, chemicals, basic metals and fabricated metal products, computer and electronic equipment, transport equipment, but for the other groups the corrected IPR was higher than the traditional one .
Argumenta Oeconomica, 2017, Nr 1 (38), s. 285-297
Keywords: international trade; import penetration; trade in value added; foreign trade of EU